The Utility of Antenatal Ultrasound in intrauterine Early Diagnosis of an Autosomal recessive Polycystic Kidney Disease in Fetus - Dinu-Florin Albu; Cristina-Crenguta Albu; Stefan-Dimitrie Albu (International Journal of Medical Research and Review, 2015)
We report a case of a 31 year old female. Ultrasound examination showed bilateral hyperechoic kidneys with multiple cysts and poor corticomedullary differentiation. The kidneys were increased in size and color Doppler showed normal bilateral renal arteries present. Amniocentesis was performed and the fetal chromosomal analysis highlighted an inversion at the 6p12.2. Further genetic investigations were done. Both parents were karyotiped and showed an inversion at the 6p12.2, typically for the PKHD1 gene location. After genetical councelling the parents decided to terminate the pregnancy. The autopsy confirmed the ultrasound findings.